Analyzing the sludge characteristics and microbial communities of biofilm and activated sludge in the partial nitrification/anammox process. (April 2022) - Zhang, Kai; Li, Jun; Zheng, Zhaoming; Zhang, Jing; Sun, Mengxia; Huang, Shan
Abstract: The implementation of anammox based process remains a challenge in treating low ammonium wastewater. In present research, partial nitrification/anammox (PN/A) performance was investigated in the integrated fixed-film activated sludge (IFAS) system. The influent of the IFAS reactor was simulated residential domestic sewage. The nitrite oxidizing bacteria (NOB)'s proliferation was observed when dissolved oxygen (DO) concentrations were 0.65 and 0.35 mg/L. By conducting intermittent aeration (aerobic 1 min/anoxic 5 min) and low DO condition (0.20 mg/L) strategy, the IFAS reactor performed good nitrogen removal performance. The average total nitrogen (TN) removing efficiency and TN removing rate reached 80.6% and 0.13 kg N/(m 3 ·d), respectively. In long term operation, extracellular polymeric substance (EPS) concentration of activated sludge was largely increased, which favored the formation of granules. The maximum frequency diameter of sludge flocs was increased to 1000 μm. The anammox bacteria and ammonium oxidizing bacteria (AOB) were both enriched within activated sludge and biofilm. High throughput analyzing result implied that anammox bacteria and AOB's abundances were 2.01% and 5.04% in activated sludge, while 2.43% and 2.45% in biofilm, respectively. Graphical abstract: Unlabelled Image Highlights: The nutrient removing performance of PN/A-IFAS reactor was investigated. The TN removing efficiency and TN removing rate reached 80.6% and 0.13 kg N/(m 3 ·d). The NOB activity was inhibited by operating low DO and intermittent aeration strategy. The AOB and anammox bacteria were both enriched in granules and biofilm. The dominant anammox bacteria and AOB were Candidatus Kuenenia and Nitrosomona .